Economic evaluation of price discounts and skill-building strategies on purchase and consumption of healthy food and beverages: The SHELF randomized controlled trial - Le, H.; Gold, L.; Abbott, G.; Crawford, D.; McNaughton, S.; Mhurchu, C.; Pollard, Christina; Ball, K. (Pergamon Press, 2016)
Objective: Pricing strategies are a promising approach for promoting healthier dietary choices. However, robust evidence of the cost-effectiveness of pricing manipulations on dietary behaviour is limited. We aimed to assess the cost-effectiveness of a 20% price reduction on fruits and vegetables and a combined skills-based behaviour change and price reduction intervention. Design and methods Cost-effectiveness analysis from a societal perspective was undertaken for the randomized controlled trial Supermarket Healthy Eating for Life (SHELf). Female shoppers in Melbourne, Australia were randomized to: (1) skill-building (n = 160); (2) price reductions (n = 161); (3) combined skill-building and price reduction (n = 161); or (4) control group (n = 161). The intervention was implemented for three months followed by a six month follow-up. Costs were measured in 2012 Australian dollars. Fruit and vegetable purchasing and consumption were measured in grams/week. Results: At three months, compared to control participants, price reduction participants increased vegetable purchases by 233 g/week (95% CI 4 to 462, p = 0.046) and fruit purchases by 364 g/week (95% CI 95 to 633, p = 0.008). Participants in the combined group purchased 280 g/week more fruits (95% CI 27 to 533, p = 0.03) than participants in the control group. Increases were not maintained six-month post intervention. No effect was noticed in the skill-building group. Compared to the control group, the price reduction intervention cost an additional A$2.3 per increased serving of vegetables purchased per week or an additional A$3 per increased serving of fruit purchased per week. The combined intervention cost an additional A$12 per increased serving of fruit purchased per week compared to the control group.Conclusions: A 20% discount on fruits and vegetables was effective in promoting overall fruit and vegetable purchases during the period the discount was active and may be cost-effective. The price discount program gave better value for money than the combined price reduction and skill-building intervention. The SHELf trial is registered with Current Controlled Trials Registration ISRCTN39432901.